2019
DOI: 10.1186/s12967-019-2014-0
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis in children: doubts and future perspectives

Abstract: Background Eosinophilic esophagitis (EoE) is a chronic immune-mediated inflammatory disorder and represents the leading cause of food impaction. The pathogenesis of EoE is the result of an interplay between genetic, environmental and host immune system factors. New therapeutic approaches for EoE have been proposed. In this manuscript we review the current evidence regarding EoE management in pediatric age, with a particular focus on new findings related to the efficacy and safety of monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…EoE can occur at any age in children. The mean age at the time of diagnosis ranges from 5.4 to 9.6 years [ 5 ]. The presentation age in our study was 9.4±4.5 years (range, 1–18 years), which is similar to that of other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EoE can occur at any age in children. The mean age at the time of diagnosis ranges from 5.4 to 9.6 years [ 5 ]. The presentation age in our study was 9.4±4.5 years (range, 1–18 years), which is similar to that of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most common endoscopic features were furrowing (82.9%), edema (74.3%), rings (47.5%), and exudates (22.9%). Normal endoscopic findings of the esophageal mucosa have been reported in approximately 32% of the children diagnosed with EoE [ 5 ]. In contrast, in the present study, visually normal esophageal mucosa was observed in only one patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial conceptualization for the presented review was derived from review articles describing the consistently disappointing results of published EoE studies that (I) attempted to identify EoE serum markers (3,4) and (II) attempted to treat EoE with parenteral biological therapies (5)(6)(7). To examine more closely if other Th2 diseases faced the same problems, four comprehensive literature searches were then conducted through January 2022, to compare EoE and three other representative Th2 diseases (asthma, AD, and CRS).…”
Section: Methods-literature Searchesmentioning
confidence: 99%
“…The most characteristic histopathologic feature of EoE is esophageal intraepithelial eosinophilia (≥15 eosinophils/HPF). Eosinophil numbers can be significant with micro‐abscesses and esophageal eosinophilia correlates with histopathologic features (including DIS and BZH) and disease severity 111,112 . In a registry of EoE patients, O'shea et al compared patients with high‐grade esophageal eosinophilia (>350 eosinophils per hpf) to patients with low‐grade eosinophilia (15–24 eosinophils per hpf) and found statistically significant differences in histologic severity, endoscopic severity and gene expression but not symptoms 113 …”
Section: Immunological Processesmentioning
confidence: 99%